2014
DOI: 10.1369/0022155414537830
|View full text |Cite
|
Sign up to set email alerts
|

Histological Evidence of Increased Osteoclast Cell Number and Asymmetric Bone Resorption Activity in the Tibiae of Interleukin-6-Deficient Mice

Abstract: SummaryInterleukin-6 (IL-6) is a multifunctional cytokine considered to modulate bone homeostasis. Based on previous contradictory studies, we aimed to verify the influence of IL-6 deficiency on bone remodeling using an IL-6 knockout (IL-6-/-) murine model. Eight-month-old male mice, homozygous for the disrupted IL-6 gene, and their wild type (WT) littermates (control), were used. After transcardiac perfusion, tibiae were removed for histochemical analysis. Compared with the control group, IL-6 deficiency incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…We have previously examined the impact of IL-6-deficiency on osteoclast formation in vivo and found that depletion of IL-6 in mice resulted in increased numbers of osteoclasts with attenuated resorptive activity, indicating separate regulation of the number and function of osteoclasts by IL-6 23 . This study therefore aimed to investigate the influence of IL-6 and sIL-6R on gradient concentrations of RANKL-induced osteogenesis and to identify the potential underlying mechanisms.…”
mentioning
confidence: 99%
“…We have previously examined the impact of IL-6-deficiency on osteoclast formation in vivo and found that depletion of IL-6 in mice resulted in increased numbers of osteoclasts with attenuated resorptive activity, indicating separate regulation of the number and function of osteoclasts by IL-6 23 . This study therefore aimed to investigate the influence of IL-6 and sIL-6R on gradient concentrations of RANKL-induced osteogenesis and to identify the potential underlying mechanisms.…”
mentioning
confidence: 99%
“…GL has a long history of well-known anti-inflammatory effects (5355), and studies show that it can inhibit the chemoattractant and mitogenic activity of HMGB1 by direct binding (52, 56). It has also been administered to patients with hepatitis B and C and is considered to be safe for human consumption (52, 57, 58), but GL may have off-target effects other than inhibition of HMGB1. The side effect of GL is mainly from its metabolic product glycyrrhetic acid after oral ingestion and catalyzed by bacteria in gut(59), which is irrelevant to IP injection of GL that we used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Bone formation is reduced, and bone remodeling is impaired in IL-6 knockout (IL-6 - / - ) mice, 70 and Harris and associates found that orbital spaceflight caused impaired osteoblast function associated with a reduction IL-6 mRNA expression. 71 Using cultures of murine osteoblasts, osteocytes, osteoclast precursors, and compressive cyclic forces, Hao and associates found that IL-6 + sIL-6R increased osteocyte-mediated osteoblast differentiation and inhibited osteoclastogenesis and osteoclast differentiation under mechanical loading via STAT3 and extracellular signal-regulated kinase (ERK) signaling pathways 72 …”
Section: Il-6 and Bone Homeostasismentioning
confidence: 99%